Exome sequencing of family trios from the National Birth Defects Prevention Study: Tapping into a rich resource of genetic and environmental data. Issue 20 (21st July 2019) - Jenkins, Mary M.; Almli, Lynn M.; Pangilinan, Faith; Chong, Jessica X.; Blue, Elizabeth E.; Shapira, Stuart K.; White, Janson; McGoldrick, Daniel; Smith, Joshua D.; Mullikin, James C.; Bean, Christopher J.; Nembhard, Wendy N.; et al.
Abstract: Background: The National Birth Defects Prevention Study (NBDPS) is a multisite, population‐based, case–control study of genetic and nongenetic risk factors for major structural birth defects. Eligible women had a pregnancy affected by a birth defect or a liveborn child without a birth defect between 1997 and 2011. They were invited to complete a telephone interview to collect pregnancy exposure data and were mailed buccal cell collection kits to collect specimens from themselves, their child (if living), and their child's father. Over 23, 000 families representing more than 30 major structural birth defects provided DNA specimens. Methods: To evaluate their utility for exome sequencing (ES), specimens from 20 children with colonic atresia were studied. Evaluations were conducted on specimens collected using cytobrushes stored and transported in open versus closed packaging, on native genomic DNA (gDNA) versus whole genome amplified (WGA) products and on a library preparation protocol adapted to low amounts of DNA. Results: The DNA extracted from brushes in open packaging yielded higher quality sequence data than DNA from brushes in closed packaging. Quality metrics of sequenced gDNA were consistently higher than metrics from corresponding WGA products and were consistently high when using a low input protocol. Conclusions: This proof‐of‐principle study established conditions under which ES can be applied to NBDPS specimens. Successful sequencing of exomes from well‐characterized NBDPS families indicated that this unique collection can be used to investigate the roles of genetic variation and gene–environment interaction effects in birth defect etiologies, providing a valuable resource for birth defect researchers.